IMPLEMENTASI DATA MINING DENGAN ALGORITMA REGRESI LINEAR SEDERHANA UNTUK MEMPREDIKSI NILAI EKSPOR DI KALIMANTAN TIMUR DENGAN APLIKASI RAPIDMINER - Rahmah, Sitti Rahmah; Fawait, Aldi Bastiatul (DiJITAC : Digital Journal of Information Technology and Communication, 2024)
This research aims to determine the development of export value in East Kalimantan. This research data utilizes secondary data obtained directly from the Central Statistics Agency of East Kalimantan Province. The analysis method applied is a simple linear regression algorithm data mining. Research findings reveal that the export value in East Kalimantan in January 2022 - April 2024 up to the predicted export value in May 2024 - December 2024 experienced a decline in the export value in East Kalimantan. With an accuracy in predicting the RMSE value of 3.182%, this means that the predicted percentage of East Kalimantan's export value is classified as very accurate. The hope of this research is that this research will become a reference for decision making for related parties, so that they can find the best strategy to increase export value in East Kalimantan. In order to realize economic improvement in East Kalimantan in the future.